Violência institucional nos crimes de estupro - Da Silva, Gabriel Augusto Sacon (2024)
The study aimed to analyze institutional violence in rape crimes, based on the bias of law 14,321/2022. In a practical way, the research was based on primordial assumptions, namely, the explanation of how institutional violence occurs, the conceptualization of revictimization and negative influence in the face of new complaints, also explaining consent and possible restriction of defense. The study is about the law and its effectiveness. The results highlight the need for complaints to combat crime, with the device in question being a great ally, with unique importance for building security and respect. By ensuring dignified and specialized treatment, with competent professionals, it is possible to increase the number of criminal communications. Thus, the justification for the research is to explain the function of the norm, to understand that its use does not cause a restriction on the adversarial process and broad defense, but leads to criminal action respecting the principle of human dignity.